EXPLORING SYNTACTIC AND CULTURAL PROBLEMS FACED BY TRANSLATORS IN TRANSLATING THE QURANIC ARABIC HOPE WORD L-AMALU لَمَألْا IN SURAHS AL-HIJR AND AL-KAHF INTO ENGLISH - Alhaj, Ali Albashir Mohammed (QiST: Journal of Quran and Tafseer Studies, 2023)
The translation of the uniqueness of the Holy Quran into English can be addressed and discussed from various linguistic and stylistic lexical, syntactic, and cultural views and standpoints. The Quranic  Arabic words/terms are vivid and magnificent with several nuances of meaning; a case which makes it difficult to be rendered accurately. This study made an effort to analyze syntactic and cultural problems faced by translators in translating the Quranic Arabic hope words l-amalu لَمَألْا in Surahs Al-Hijr and Al-Kahf into English. The findings of the study showed that the translators of the Holy Quran into English faced cultural problems because Quranic Arabic culture-specific terms have no counterpart in the English culture. Also, part of the difficulties and quandaries in rendering such terms exists in the fact that these words need an awareness of the Arabic-Islamic culture with all its religious values and mores. The findings of the study also brought to light that the Quranic Arabic hope words l-amalu لَمَألْا are culture-specific par excellent. They denote a type of translation inequivalent because they cannot be adequately rendered by offering their denotative meanings.